Effectiveness of total quality management in marketing performance and the role of continuous improvement as a mediator for Iraqi institutions (Czech Journal of Multidisciplinary Innovations, 2025)
Current study aims to investigate Total Quality Management (TQM) and its potential outcomes in the Iraqi governmental institutions sector. The study focused on a major problem to understand the possible variables for achieving successful Total Quality Management that leads to positive outcomes on the behaviors of Iraqi institutions. The research also focused on previous studies of scientific research in clarifying the impact of Total Quality Management determinants as an independent factor (improving training, work team, cultural change, full employee participation) on marketing performance as a dependent factor (focus on opportunity, calculated risk, value creation) and the importance of continuous improvement (organizational performance, individual performance, procedure performance) as an independent variable in this research. A sample of employees in Iraqi governmental institutions, which numbered (98), and (4) questionnaire forms were incorrect, and the net valid forms obtained by the researcher were (94). The study problem focused on the possibility enhancing impact of (TQM) as an independent factor on marketing performance as a dependent factor and the role of continuous improvement as an intermediary factor. The statistical methods (SPSS) were used and this study presented many recommendations to strengthen the relationship between employees in Iraqi governmental institutions. This study gives employees the impression that the relationship between the two parties depends on cooperation and consideration between governmental institutions.